Peran aktivitas reverse engineering pada Jurusan Teknik dan Desain di perguruan tinggi - Tubagus Ahmad Dwinandana P. (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Product design is a complex activity because it is a cross of various fields. Lecturing this activity in universities is also a challenge for lecturers because these activities require not only knowledge but also experience. On the other hand, the industry expects human resources that are compatible with industrial standards. The Reverse Engineering (RE) method is one solution to this problem. This qualitative-descriptive research with the literature study method aims to determine the role of reverse engineering in engineering and design education, especially in product design subject. The author conducted the study from the book and science journal source to define the aspect related to RE activity in engineering and design education. According to this research, it can be concluded that the RE method has a role in providing knowledge about various aspects of the design of some products through the practice of disassembling and evaluating existing products. Then this method also has a role in providing knowledge through practice in designing a product. Various equipment, both hardware and software are required in this method. The challenges that arise are related to the limited cost of procuring sample products and workshop facilities and limited lecture time.